Na práxis da assessoria jurídica universitária popular: extensão e produção de conhecimento - Miranda, Carla (2010)
We make a reflection of a social practice called University Popular Juridical Assessory (AJUP), of our ajupianas practices, of what explicit the statements of its members on its main feature: its capacity for a critical and emancipatory law, a critical and emancipatory university and a critical and emacipatory society, We rescued its theoretical framework on the historical experience of theoretical and practical movements of the critical law from the 1980s and 1990s. But in the context of the university where it happens nowadays, we speak of practice as a university extension, a mark of its political transformative intention, and we identify it with the popular movement of the extension. This characterization, as a practice, highlights the requirement for production of socially useful knowledge in the extension. This characterization emphasizes the popular education as a methodology, but with the multiplicity of meanings that the term includes nowadays, it is necessary understand at the methodological moments the implementation of this practice, our real approximation of the union between theory and practice. In this sense, the systematized experience show us the one hand, the outline of their own way of doing popular extension popular with the Law: a practice with a greater community insertion, where the research is not a preview, but part of the same action, and recognizes that other legal sociability, besides the official ones. But the systematized experience also shows us, however, our difficulties even in this dialogic exercise with the people, in this work guided by an emancipator ethical sense. Thinking practices in an ethical sense is to recognize that every practice brings a social theory (as a way of being, being and knowing), and produces knowledge and transformation (albeit conservatively) in the reflexivity of these modes of relating in the world and with the world. In other words, our practices, as well as the knowledge we produce because of them, are closely related to a model of civilization. It is here that talk about AJUP as a popular extension in law, and about the necessary production of useful knowledge in this practice, takes up the debate on the values in the knowledge. The experiences demonstrate a useful knowledge, produced in the social practice, in relational way in the existential situations of life. And it's acknowledging rationalities different from the rationality of modern science that the popular extension questions deeply the university. The understanding of our difficulties is the recognition that our practices often reproduce the dominant and dominating ethic we criticize, especially when we don t reflect on our cultural conditioning that we are also immersed. In our case, the AJUP, it is important to recognize the limits of our "vision of law", and also the vision of "our law". In this sense, a practice in an ethical-liberator sense means more an attitude of constant questioning of ourselves and our relations with the world, than the reproduction of any model of "emancipatory" practice. It's in fact, an exercise of a profound self-criticism, of ourselves and our practices, that guides us to bridge the gaps between our say and our doing, for the concrete realization of a liberating practice and in a University Popular Juridical Assessory.